Vortex interactions between forewing and hindwing of dragonfly in hovering flight. Issue 1 (January 2015) - Xie, Chun-Mei; Huang, Wei-Xi
Abstract: Two tandem flapping wings in viscous flow were modeled by using the immersed boundary method for exploration of the aerodynamics of dragonfly in hovering flight. Interaction between the forewing and the hindwing, and its effect on the lift forces, were examined by varying the phase difference of the wing motions and the inter-distance of the two wings. Two vortex interaction modes were identified at different phase differences and inter-distances, which give rise to significant variations of the lift forces. The first interaction mode increases the lift of the forewing and the second one enhances the lift of the hindwing. The two modes occur at different time during a flapping period and have different influence on the lift of wings as the phase difference varies.